2013
DOI: 10.1002/jps.23730
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Biophysical Analysis and Data Visualization of Conformational Stability of an IgG1 Monoclonal Antibody After Deglycosylation

Abstract: The structural integrity and conformational stability of an IgG1 monoclonal antibody (mAb), after partial and complete enzymatic removal of the N-linked Fc glycan, was compared to the untreated mAb over a wide range of temperature (10° to 90°C) and solution pH (3 to 8) using circular dichroism, fluorescence spectroscopy, and static light scattering combined with data visualization employing empirical phase diagrams (EPDs). Subtle to larger stability differences between the different glycoforms were observed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 62 publications
(171 reference statements)
3
34
0
Order By: Relevance
“…Dynamics-The conserved antibody glycosylation in the Fc domain is important for the structural integrity of antibodies, and partial or full deglycosylation has been shown to influence conformation, storage stability, and solubility (46,47). The impact of antibody glycosylations on HDX-MS was examined previously (40,48), and in our study on Ab wt and Ab degly we observed effects upon antibody deglycosylation similar to those seen in prior studies performed on another IgG 1 antibody.…”
Section: Impact Of Antibody Deglycosylation On Conformation Andsupporting
confidence: 75%
“…Dynamics-The conserved antibody glycosylation in the Fc domain is important for the structural integrity of antibodies, and partial or full deglycosylation has been shown to influence conformation, storage stability, and solubility (46,47). The impact of antibody glycosylations on HDX-MS was examined previously (40,48), and in our study on Ab wt and Ab degly we observed effects upon antibody deglycosylation similar to those seen in prior studies performed on another IgG 1 antibody.…”
Section: Impact Of Antibody Deglycosylation On Conformation Andsupporting
confidence: 75%
“…30 It is possible that the increased flexibility of the peptide backbone disrupts the packing interactions between the peptide backbone and the glycan chains, leading to unfolding of this hydrophobic segment. This unfolded apolar segment, in turn, may act as a hotspot for subsequent structural alterations that could lead to irreversible aggregation in IgG1 mAbs, [55][56][57] for example, as observed by SEC analysis in this study. Limiting the flexibility of this particular segment may therefore serve as a good indicator for designing mAbs (and mAbrelated products such as IgG-Fc, fusion proteins, or antibody drug conjugates) with higher thermostability and resistance to aggregation.…”
Section: Discussionmentioning
confidence: 56%
“…A series of sequentially truncated glycoforms of IgG1 Fc (Figure 1), which differ only in the size of the N-linked glycan at N297 or a single conservative amino acid mutation (N297Q), were chosen as members for the model system. Previous studies have indicated that these glycoforms would display a range of biological activities and physical properties 1,32,45 that would be advantageous for our biosimilarity studies.…”
Section: Introductionmentioning
confidence: 99%